2006
DOI: 10.1111/j.1748-5827.2006.00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical resection of a primary tracheal fibrosarcoma in a dog

Abstract: A four-year-old, entire male Rottweiler was presented with a history of respiratory distress. A tracheal mass was diagnosed on thoracic radiographs and tracheoscopy. Surgical excision of three tracheal rings incorporating the tumour was performed. The mass was found to be a low-grade fibrosarcoma. Twenty-four months later, the owner reported that there was no recurrence of respiratory distress and the dog appeared to be doing well clinically. This case of primary tracheal fibrosarcoma suggests that this type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
0
8
0
2
Order By: Relevance
“…Primary fibrosarcomas of the intestine itself are extremely rare in dogs and other animal species (Goldschmidt and Hendrick 2002), and may originate anywhere in the body (Orr 1984;Mahler et al 2006;Speltz et al 2007;Govaere et al 2010). To the authors' knowledge, to date only one case has been reported in the veterinary literature, in which a tumour was described in a 17-year old Cocker Spaniel (Hurov 1962).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Primary fibrosarcomas of the intestine itself are extremely rare in dogs and other animal species (Goldschmidt and Hendrick 2002), and may originate anywhere in the body (Orr 1984;Mahler et al 2006;Speltz et al 2007;Govaere et al 2010). To the authors' knowledge, to date only one case has been reported in the veterinary literature, in which a tumour was described in a 17-year old Cocker Spaniel (Hurov 1962).…”
Section: Discussionmentioning
confidence: 92%
“…The skin and subcutis are the primary sites of occurrence of fibrosarcomas in dogs and other domestic animals (Goldschmidt and Hendrick 2002), but these can develop anywhere in the body such as the heart (Speltz et al 2007), liver (Gallati 1956), kidney (Brown et al 1975), urinary bladder (Olausson et al 2005), uterus (Govaere et al 2010), omentum (Rayner et al 2010), trachea (Mahler et al 2006) and, on rare occasions, in the mammary gland (Orr 1984). Primary malignant intestinal tumours are rare in dogs, and they may cause clinical signs of luminal obstruction, intestinal dysfunction and intestinal ulceration and/or perforation, resulting in septic peritonitis (Larock and Ginn 1997;Head et al 2002).…”
mentioning
confidence: 99%
“…Les auteurs rapportent que la masse a été visualisée avec détail par laryngoscopie. Les observations de deux cas plus récents illustrent la pertinence de cet examen qui a permis de localiser, de latéraliser et de détailler l'aspect de la lésion [4,5]. Enfin, l'endoscopie fut le seul examen complémentaire employé avant le retrait chirurgical d'une masse arythénoï-dienne gauche chez un chien [1].…”
Section: Discussion L'apport De L'imagerie Médicale Dans Le Diagnostiunclassified
“…Applying a silicone stent to canine tracheal collapse will eliminate the shortcomings associated with metallic stents. Like in human medicine [5,18,23], the silicone stent could also be used for tracheal tumor or tracheal stenosis, although these conditions are rare in veterinary medicine [1,2,11,14].…”
mentioning
confidence: 99%